Analisis Peran Shipping Agent PT. Maritim Indo Trans dalam Meningkatkan Efisiensi Operasional Shipping Line May Tanker SDN BHD di Pelabuhan Ciwandan - Luthfiah Samsir; Muhammad Aksar; Dewi Pusparini (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to analyze the role of the shipping agent PT. Maritim Indo Trans in improving the operational efficiency of the shipping line May Tanker Sdn Bhd at Ciwandan Port. This research is motivated by the importance of ship operational efficiency in reducing port stay time and operational costs, in which the shipping agent plays a strategic role as a liaison between the ship and the port authorities and related agencies. The research method used is descriptive qualitative with data collection techniques through observation and documentation. The data obtained were analyzed to identify the role of the shipping agent and the factors influencing its performance on ship operational efficiency. The results show that PT. Maritim Indo Trans has carried out its agency role quite optimally, including managing ship documents, coordinating with relevant agencies, and supervising loading and unloading activities. The implementation of this role contributes to improving operational efficiency as indicated by reduced waiting time, turnaround time, and port stay. However, the effectiveness of this role is still influenced by internal factors such as limited human resources and suboptimal internal coordination, as well as external factors such as weather conditions, limited port facilities, and congestion of activities at the dock.